Effectiveness of a medical exercise prescription to promote physical activity in children: a pragmatic randomized trial in primary care - Morillas-Mingorance, Ángel; Garach Gómez, Ana; Gutiérrez García, Iván; Monereo Moreno, Isabel; Sánchez Ruiz-Cabello, Francisco Javier; Maldonado, Jose (Frontiers in Pediatrics, 2026)
ObjectivesMost children fail to meet international physical activity (PA) recommendations. Can a single pediatric visit help reverse this trend? Brief counseling is infrequently used in clinical practice and its actual impact on children's activity levels remains uncertain. This study evaluates the impact of medical exercise prescriptions on children's PA levels compared to standard health advice. It also explores whether these prescriptions contribute to reducing daily screen time.Study designA randomized controlled trial was conducted with 130 children aged 6–14 years. Participants were randomized into two groups: one received brief standard health advice (HA, 2 min), and the other received a 10-minute intervention including a written medical exercise prescription (MEP). All sessions were delivered by three trained pediatricians following a standardized protocol. PA levels (duration and intensity), screen time, and anthropometric data were collected through the same questionnaires. Physical activity was assessed at 3 and 12 months by the same investigator. Multivariate analyses were performed to evaluate changes over time.ResultsBoth interventions increased the duration and intensity of physical activity, with a significant increase in the number of children classified as physically active. An inverse relationship was observed between physical activity and screen time, indicating that promoting exercise may help reduce sedentary behavior. Parental satisfaction was high and similar in both groups, suggesting good acceptance of the interventions regardless of their format or duration.ConclusionsA short, focused message from a pediatrician—delivered in just a few minutes—can lead to lasting improvements in children's activity levels and screen habits. Brief health advice was as effective as personalized prescriptions, offering a simple, feasible and low-cost strategy to promote healthier lifestyles in primary care.Clinical Trial Registrationhttps://register.clinicaltrials.gov/prs/beta/studies/S000F96J00000036/recordSummary, identifier NCT06765460.